Examination of DON-toxin content of milling by product generated after color sorting - Kecskésné-Nagy Eleonóra (Analecta technica Szegedinensia, 2019)
Thanks to the favorable impact of vintage effect occurring in recent years the Fusarium contamination of wheat and consequently a high DON-toxin concentration is often caused problem. The DON-toxin in terms of human and animal health is a serious food safety risk factor. Therefore, it is important that there are methods during the wheat milling process which reduces the level of toxin. We confirmed in our earlier examinations, that with the help of modern color sorting machine the DON-toxin content of wheat items is effectively can be reduced. The question is, during the process how parallel changes the mycotoxin content of by-products, which are used primarily as animal forage. The authors are presented an analysis of these relevant experimental data. The results show, that the toxin content of the byproduct is exceeds the starting wheat item's toxin content. However, the result of the regression analysis shows that no correlation in the toxin contents between the starting raw material, purified wheat and by-product. This should be considered to the users when they would like to utilize the by-product as ingredient of forage or feedstuff.